Short-term power output and local muscular endurance of young male soccer players according to playing position - Nikolaidis, P. T. (Collegium Antropologicum, 2014)
Although the contribution of anaerobic power in soccer performance is recognized and there is evidence that many anthropometric and physiological characteristics vary according to playing position, the association between playing position and short-term power output, and local muscular endurance is not well studied, especially in young players. Therefore, the aim of the present study is to examine whether this component of sport-related physical fitness of young soccer players varies according to playing position. Young male (N=296; aged 10.94-21.00 y), classified in five two-year age-groups, and adults (N=30; aged 21.12-31.59 y), all members of competitive soccer clubs, performed the 30-s Wingate anaerobic test against braking force 0.075 kg.kg-1 of body mass. One-way analysis of variance (ANOVA) revealed significant differences between age groups with regard to peak power in absolute, Ppeak (F5,320=86.7, p<0.001), and in relative to body mass values, rPpeak (F5,320=43.27, p<0.001), mean power in absolute, Pmean (F5,313=108.97, p<0.001), and in relative values, rPmean (F5,313=41.64, p<0.001), while there was no difference with respect to fatigue index, FI (F5,312=1.09, p= 0.370). One-way analysis of covariance, considering age as covariate, did not reveal any significant differences among playing position groups with regard to Ppeak (F3,289=1.46, p=0.226), rPpeak (F3,289=0.87, p=0.457) and Pmean (F3,283=0.31, p=0.817), while goalkeepers had lower rPmean than defenders, midfielders and forwards (F3,283=6.32, p<0.001). One-way ANOVA revealed differences with regard to FI (F3,283=5.97, p<0.001), according to which goalkeepers had higher values than defenders and midfielders. Compared with data from previous studies in general population, participants had superior short-term power output and local muscular endurance. Both these anaerobic parameters were in direct relationship with age (r=0.64, p<0.001, and r=0.68, p<0.001 respectively), even when the influence of body mass was partitioned out (r=0.50, p<0.001 in both cases). The comparison between playing positions revealed similar alactic anaerobic profile for all groups, and indicated local muscular endurance as the anaerobic parameter that discriminated goalkeepers from outfield players.